2019
DOI: 10.1097/corr.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

A Single Positive Tissue Culture Increases the Risk of Rerevision of Clinically Aseptic THA: A National Register Study

Abstract: Side 4Forord DHR's styregruppe praesenterer hermed årsrapporten for 2016. Der er nu i perioden 1995-2015 i alt indberettet ca. 150.000 primaere og 23.400 revisioner til DHR. DHR har laenge levet op til de gaeldende krav for indrapportering.Dette års komplethedsgrad på 97,5 % for primaere THA er meget tilfredsstillende, mens kompletheden for revisions THA er på 90,3 % og såfremt at der fratraekkes revision af hemialloplastik stiger det til 94,4%. Da standarden er 95% er det ikke tilfredsstillende. Der skal lyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…Whereas low-grade PJI is mostly presenting with early loosening, or pain only, it can be very difficult to diagnose. During recent years, we have become increasingly aware that, in addition to obvious PJI, there is an important but unknown number of septic failures-PJI hiding within "aseptic failure" cohorts [5][6][7]. Recent papers are presenting significant numbers of up to 20% of lowgrade PJI within presumed aseptic failure cohorts [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas low-grade PJI is mostly presenting with early loosening, or pain only, it can be very difficult to diagnose. During recent years, we have become increasingly aware that, in addition to obvious PJI, there is an important but unknown number of septic failures-PJI hiding within "aseptic failure" cohorts [5][6][7]. Recent papers are presenting significant numbers of up to 20% of lowgrade PJI within presumed aseptic failure cohorts [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, we have become increasingly aware that, in addition to obvious PJI, there is an important but unknown number of septic failures-PJI hiding within "aseptic failure" cohorts [5][6][7]. Recent papers are presenting significant numbers of up to 20% of lowgrade PJI within presumed aseptic failure cohorts [7,8]. Many early failures after revision TJA fit within this overlooked PJI group [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The present study reported an incidence of unexpected PJIs of 20%. This value is higher compared to what previously reported in the literature [7][8][9][10][11][12][13], particularly for the THA revision (22.4% versus 12.1%) compared with TKA revision (11.1% versus 7.9%) [9]. The discrepancy is mostly due to the heterogeneity of the criteria for defining an unexpected PJI.…”
Section: Discussionmentioning
confidence: 57%
“…Since the diagnosis often results from the data collected during surgery, the incidence of PJIs is likely higher than reported by joint registries. Previous authors reported that the rate of PJIs in patients undergoing aseptic Level of evidence: level IV, case series revision arthroplasties ranges from 6 to 13.5% [7][8][9][10][11][12][13]. However, the outcome of patients with unexpected positive intra-operative cultures during prosthetic revision surgery for presumed aseptic failure is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation